Mineral status of Java thin-tailed sheep grazed in Mijen agriculture area, Semarang, Indonesia - Widiyanto, W.; Kusumanti, E.; Mulyono, M.; Surahmanto, S.; Ismadi, V. D. Y. B. (Journal of the Indonesian Tropical Animal Agriculture, 2017)
The objective of this study was to study the mineral status of Java thin-tailed (JTT) sheep grazed in Mijen-Semarang, Central Java. Six month old of male JTT sheep and paddock with field grass vegetation were used in the research. Fifteen male JTT sheeps were divided into three groups consisting of 5 heads per group, and grazing for 2 month (in early rainy season, late rainy season and dry season, respectively). The measured variables were feed consumption, digested organic matter, mineral (calcium, phosphorus, magnesium, copper, zinc) level in forage, feces, blood, and daily body weight gain. The data were analyzed by analysis of variance with one-way classification. Magnesium and zinc status of JTT sheep were adequate, whereas phosphorus status was deficient in all season. Calcium in early and late rainy season were deficient (7.37 and 7.86 mg/100 mL, respectively), whereas in the dry season was adequate (8.70 mg/100 mL). The copper deficiency was found in dry and late rainy season (with the Serum copper level was 0.62 and 0.51 µg/mL, respectively, and borderline in early rainy season (64.7 µg/mL). Serum copper in the late rainy season was lower (P<0.05) than it in early rainy season and dry season. There were seasonal variation of mineral status of Java thin-tailed (JTT) sheep grazed in Mijen agricultural area, Semarang, Central Java.